PEMBERDAYAAN EKONOMI MELALUI PEMBIAYAAN MURABAHAH PADA KJKS BMT AMANAH SEJAHTERA PADANG SELATAN - Yummil Hasan; Syahril Nanda Kurniawan; Elsanra Eka Putra; Hermawati Hermawati (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Murabahah product KJKS BMT, to assist in empowering small community businesses to provide business capital through the distribution of financing funds. After the financing is disbursed and distributed, problems begin to arise in returning the financing, where many customers are unable to pay off their obligations. In terms of the procedure for implementing the empowerment of murabaha product financing, it has been distributed in accordance with the SOP, there has even been a rescue attempt, but it is still recorded as a failure, due to the many excuses and reasons from customers. According to the data, it is stated that the percentage of non-performing financing continues to grow. This survey uses a qualitative survey method. It is said in the results of the research on empowerment of financing distribution that has been carried out in accordance with the procedure, starting from the submission, analysis with the 5C stage, to the disbursement stage. However, in its implementation there are difficulties, due to the lack of understanding of prospective debtors about the procedures and lack of knowledge of debtors about their obligations to pay their debts. Other causes are the increase in fuel prices, a decrease in operating income, and the incitement from third parties not to have to pay back. Meanwhile, other efforts to save the non-performing financing, namely KJKS BMT have established and carried out several actions and procedures, such as telephone notification, sending the first invoice, direct collection by the manager, foreclosure of collateral. Another solution is to increase supervision over the distribution of financing funds, and add KJKS BMT operational staff who are competent in the field of financing collection.